Fabrikasi dan Karakterisasi Elektroda untuk Sistem Capasitive Deionization(CDI) pada Proses Desalinasi Larutan NaCl dengan Metode Freezing-Thawing - Iim Fatimah, Endarko (Jurnal Teori dan Aplikasi Fisika, 2013)
An electrode has been made for capacitive deionization (CDI) technology during the process of desalination of NaCl solution using freezing-thawing method. The electrodes are made of a combination of coconut shell activated carbon, graphite and polyvinyl alcohol by varying the material composition and the number of cycles during the freezing-thawing process. Carbon electrode test results using cyclic voltametric method showed the peak of oxidation reduction in its voltamogram cyclic which is the peak of cathode current 0.6 mA on potential reduction of - 0.6 V therefore the electrode has a capacitance per unit area of 0,14 F/g. Electrode test results show that the greatest capacitance and the highest electrode porosity obtained on the composition of the activated carbon of coconut shell: polyvinyl alcohol (PVA): graphite is 18 : 1: 6. In this research the system were arranged in a monopolar and bipolar to compare the efficiency of the reduction of the salt level. Based on the tests carried out, monopolar arranged structure shows 37% of salt levels reduction in five minutes while the bipolar arranged structure only able to reduce salt levels of about 20 % in five minutes. It showed that the monopolar arranged structure is able to give a better outcome. Keywords: hydrogel PVA, carbon,capasitive deionization, cyclic voltametri, desalination.